The Occurrence of Priapism as a Result of the Use of a Single Dose of Quetiapine - Fatih Ozkaya; Tevfik Ziypak; Senol Adanur; Atakan Yucel; Unsal Aydinoglu (Eurasian Journal of Medicine, 2012)
Priapism is a prolonged pathologic erection situation that occurs after sexual stimulation or without sexual stimulation. This condition is divided into two types, ischemic (low-flow, veno-occlusive) and non-ischemic (high-flow, arterial). A 68-year-old male patient applied to our clinic with the complaints of hardness and pain in the penis. Three days before he applied to our clinic, he was prescribed a single dose of 200 mg quetiapine by a psychiatry polyclinic for the complication of insomnia. Nearly 6 hours after the first dose of quetiapine, an involuntary erection occurred with accompanying pain in the penis. The patient waited for spontaneous detumescence without consulting a psychiatrist. After the patient had waited for 48 hours without any change, he applied to our clinic. Other etiologic factors of priapism were excluded (such as malignancy, blood dyscrasia, leukemia, and trauma). In blood gas samples obtained from the corpus cavernosum, hypoxia, hypercarbia, and acidosis were diagnosed. Ischemic priapism was supposed. We conclude that priapism can be viewed as a new possible side effect of quetiapine and that patients should be warned about this side effect.